Climate change, aeroallergens, and the aeroexposome - Paul J Beggs (Environmental Research Letters, 2021)
Allergic diseases are a major public health problem globally and are increasing. The impacts of climate change on aeroallergens such as pollen and fungal spores and allergic respiratory diseases such as allergic asthma and allergic rhinitis have been considered since the early years of climate change and human health research, and exploration of this topic has accelerated over the past decade or so. This review examines the impacts of climate change on aeroallergens, including interactions with air pollutants, and the resulting impacts on allergic respiratory diseases. It discusses mitigation and adaptation in this context. It does this with a focus on advances over the last 2 years (2019 and 2020) to highlight research at the frontier of this field. It also explores the growing recognition of the need for a more holistic and integrated approach to environmental monitoring and exposure and presents the concept of the aeroexposome as a frame through which these impacts of climate change and responses to them could be viewed moving forward. As the evidence of impacts of climate change on aeroallergen production and atmospheric concentration, seasonality, distribution, and allergenicity mounts, crucial research demonstrating the resulting impacts on health outcomes such as aeroallergen sensitisation prevalence, asthma emergency department visits, and asthma hospitalisations is now emerging. It is vital that the momentum of the last decade continue with research to fill the many gaps that remain in our knowledge of this complex topic—refining analytical techniques, broadening the geographical coverage (to include, for example, the Southern Hemisphere), and more explicitly exploring the impacts of climate change on indoor aeroallergens.